1996
DOI: 10.1002/chin.199614170
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: N‐3‐Substituted Pyrimidinones as Potent, Orally Active, AT1 Selective Angiotensin II Receptor Antagonists.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…1,4 It can be observed that Prazosin, Terazosin and Doxazosin have a pyrimidine ring in their chemical structures. 4 In fact, pyrimidines and their oxo-derivatives are described in the literature as presenting a wide array of biological activities such as antitumor, 6,7 interferon inducer, 8 antiviral, 9 anti-hipertensive, 10 hypoglycemic, 11 anticonvulsant, 12 antinociceptive, 13,14 and anti-inflammatory. 15 Pyrimidine or pyrimidinone rings can be synthesized in several ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 It can be observed that Prazosin, Terazosin and Doxazosin have a pyrimidine ring in their chemical structures. 4 In fact, pyrimidines and their oxo-derivatives are described in the literature as presenting a wide array of biological activities such as antitumor, 6,7 interferon inducer, 8 antiviral, 9 anti-hipertensive, 10 hypoglycemic, 11 anticonvulsant, 12 antinociceptive, 13,14 and anti-inflammatory. 15 Pyrimidine or pyrimidinone rings can be synthesized in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…This whole process may take two days of laboratory work for the preparation of one product. [9][10][11]14,18 These findings encouraged us to search new ways to perform these reactions and to evaluate the biological activity of these heterocyclic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Sartans are a new class of antihypertensive drugs acting as Ang II receptor antagonists. Examples of thiophene-containing sartan derivatives are milfasartan (E), which has reached the phase I of clinical trials, 8 and eprosartan (F), marketed in some countries under the tradename Teveten ® , used in the treatment of arterial hypertension (…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Fu and co-workers have shown that 2-bromocycloalk-1-enecarboxylic acids couple and cyclize with amidine hydrochlorides in the presence of copper(I) iodide to give bicyclic pyrimidinones. 8 A similar coupling and cyclization of 2-bromocyclohex-1-enecarboxylic acid with amidine hydrochlorides to give bicyclic pyrimidinones can be induced by a magnetite (Fe 3 O 4 ) nanoparticlesupported copper(I) catalyst.…”
mentioning
confidence: 99%
“…Because the pyrimidinone ring plays an important role as a basic scaffold component in numerous biologically active compounds, many pyrimidinone-containing compounds have been synthesized and tested for biological activity. [1][2][3][4][5][6][7] Fu and co-workers have shown that 2-bromocycloalk-1-enecarboxylic acids couple and cyclize with amidine hydrochlorides in the presence of copper(I) iodide to give bicyclic pyrimidinones. 8 A similar coupling and cyclization of 2-bromocyclohex-1-enecarboxylic acid with amidine hydrochlorides to give bicyclic pyrimidinones can be induced by a magnetite (Fe 3 O 4 ) nanoparticlesupported copper(I) catalyst.…”
mentioning
confidence: 99%